Orthopaedic biofilm infections. Issue 4 (April 2017) - Zimmerli, Werner; Sendi, Parham
Abstract : Many infections of the musculoskeletal system are biofilm infections that develop on non‐living surfaces. Microorganisms adhere either on dead bone (sequesters) or implants. As a rule for a curative concept, chronic osteomyelitis or implant‐associated bone infection must be treated with a combination of surgery and antimicrobial therapy. If an implant is kept in place, or a new device is implanted before complete healing of infection, a biofilm‐active antibiotic should be used. Rifamycins are active against biofilms of staphylococci, and fluoroquinolones against those of Gram‐negative bacilli. In this review, the management of chronic osteomyelitis, periprosthetic joint infection and implant‐associated osteomyelitis of long bones is presented.